The struggle of wadas residents: the contribution of muhammadiyah and nu in maintaining environmental sustainability and social justice - Ramadhan, Sukma Aditya; Suswanta, Suswanta; Al Hamdi, Ridho; Fadli, Yusuf; Isbandi, Fitri Susiswani (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Wadas Village in Purworejo faces environmental destruction due to planned andesite mining for the Bener Dam, threatening local resources and the community's socio-economic life. Muhammadiyah and NU play key roles in supporting residents' efforts to protect the environment and social justice. This study examines their involvement in maintaining environmental sustainability and social justice in Wadas Village, focusing on their contributions to organizing the community. A qualitative approach with a case study method was used in this research. Data were collected through in-depth interviews with residents, Muhammadiyah and NU members, and observations of advocacy activities and actions carried out by both organizations. The data were analyzed thematically. The findings show that Muhammadiyah and NU are actively involved in legal advocacy, scientific research, and religious activities, such as mujahaddah at local mosques, to build social awareness and strengthen the residents' resistance to harmful policies. The struggle of Wadas residents is closely linked to the active roles of Muhammadiyah and NU in fostering social solidarity, collective awareness, and environmental sustainability advocacy. This study highlights the significant contribution of religious organizations in social and environmental movements and their influence on public policies favoring the community.